Telaahan Penerapan Sistem Informasi Akuntansi Berbasis Komputer Akuntansi (Menggunakan Microsoft Excel) dalam Penyajian Laporan Keuangan (Studi Kasus pada Rumah Sakit Islam Bogor) - Syarief Gerald Prasetya (Jurnal Ilmiah Binaniaga, 2010)
Hospital was established to serve the medical needs of the citizen. In addition to serving, hospitals also need to explore the benefits for the sustainability and the development of the hospital. To achieve financial reports have involved a large role. Accounting information system computer-based accounting will help serving the financial reports, so that more accurate and faster. Errors can be diminished.  Research object is selected by the author to conduct research is Bogor Rumah Sakit Islam. A hospital that is located on Jl. Perdana Raya. 22 Budi Agung, Jakarta Utara. This hospital was established on May 12, 1991. The location is strategic as it is in the center of Bogor. In doing activity, accounting information system based on computerized accounting still not yet common use. Computer already exist but support application to create an accurate and fast financial statement does not exist. So much weaknesses if we still using manual method. Like slowly processing data, still using much worker and much step while processing. The information result is still contained high mistake. To solve all problems above we need accounting software as tool for accounting division. For that I try to apply computerized accounting using Microsoft Excel for helping creating financial statement. By doing observation and interview with related employee, this research can do well. Journalize transaction process by using Microsoft Excel is to make a column for each transaction such as Journal Voucher, General Ledger, Balance Sheet. After making a column, the next step is inputing achievement data to Journal Voucher. After inputing data, General Ledger and Balance Sheet can automatically fill up. By using computer, processing data is more faster, information result is more accurately, human resource is less needed. Related management can get information they need more faster, because amount recalculated every doing transaction.